2020
DOI: 10.2174/1574892815666200713145931
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stem Cells and their Management in Cancer Therapy

Abstract: Background: In the last decade, the proposed Cancer Stem Cell (CSC) hypothesis has steadily changed the way we are approaching cancer treatment. CSCs may be the source of the heterogeneous non-tumorigenic cell population included in a neoplasm. Intratumor and intertumoral heterogeneity is a well-known phenomenon that massively entangles the diagnosis and treatment of cancer. The literature seems to suggest that heterogeneity develops progressively as tumorinitiating stem cells. CSCs harbor genetic and/or epige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 125 publications
0
5
0
Order By: Relevance
“…CSCs are a subset of cancer cells with self-renewal ability ( Shenouda et al, 2020 ; Carvalho et al, 2021 ). They play a critical role in cancer initiation and progression and are naturally resistant to anticancer agents, which cause cancer recurrence and MDR ( Aravindan et al, 2019 ; Fong et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CSCs are a subset of cancer cells with self-renewal ability ( Shenouda et al, 2020 ; Carvalho et al, 2021 ). They play a critical role in cancer initiation and progression and are naturally resistant to anticancer agents, which cause cancer recurrence and MDR ( Aravindan et al, 2019 ; Fong et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…CSCs are a set of sub-population cells with self-renewal and differentiation characteristics, possibly contributing to tumor formation and relapse ( Shenouda et al, 2020 ). CSCs are naturally drug-resistant, possibly due to their intrinsic property and strengthened defensive weapons compared to non-CSCs ( Carvalho et al, 2021 ; Fong et al, 2021 ; Miyoshi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intratumor and intertumoral heterogeneity is now well-established, and they bring in huge challenges in the diagnosis and treatment of neoplasia. The literature seems to suggest that heterogeneity arises gradually as tumor-initiating (carcinoma) stem cells (18). They harbor genetic and/or epigenetic changes that permit them to serially separate into multiple tumor cell types.…”
Section: Heterogeneity Conundrum and The In-situ Neuroblastomamentioning
confidence: 99%
“…CD13, a biomarker of human liver CSCs, which is associated with the self-renewal, differentiation potential, signal transduction, drug resistance, recurrence and prognosis of liver cancer stem cells (LCSCs) ( Christ et al, 2011 ; Kim et al, 2012 ). CSCs possess stem cell-like properties, including the ability for self-renewal and CSCs can start carcinogenesis and are responsible for tumor recurrence after treatment ( Shenouda et al, 2020 ). Our previous studies have confirmed that inhibition of CD13 could increase the sensitivity of HCC cell to 5FU and reverse their drug resistance, thereby indicating that CD13 is potential therapeutic target.…”
Section: Dicussionmentioning
confidence: 99%